The history of the vaccine and its benefits (Research, Society and Development, 2024)
Vaccination is one of the greatest advances in medicine as a method of preventing diseases. Its first records occurred through a practice known as variolation. In 1798, Edward Jenner infected some healthy people with the smallpox virus, and observed the causal relationship between smallpox disease and its contagion. This work aims to describe the history of vaccination, its origin, types of immunization and global pandemics, with emphasis on COVID-19, as a way of gathering information to create an illustrated book. A narrative review was carried out through the analysis of articles, books and other works published on the internet. Despite all the scientifically proven benefits, vaccine hesitancy has occurred since its inception and is growing worldwide. In 2019, a large part of the world's population was infected by the SARS-CoV-2 virus, and this fact led to the emergence of the COVID-19 pandemic, which tested the human capacity to produce vaccines, while at the same time highlighting the low understanding about such methods by some individuals or groups from different civil societies. Since then, anti-vaccine rhetoric has been gaining ground, guiding the media debate and negatively impacting vaccination adherence at different stages of life, with emphasis on children, who are subordinate to family members in receiving vaccines. It is concluded that the history of vaccination is a complex topic due to its historical context of emergence and historical-scientific processes, often making it difficult to understand the topic, equipping groups that oppose vaccination practices.